A pharmacist-led interprofessional education program for family practice medical residents specializing in HIV care - Naccarato, Mark; Yoong, Deborah; Gough, Kevin; Tseng, Alice; Arbess, Gordon (Canadian Medical Education Journal, 2023)
Implication Statement We developed a pharmacist-led one-month teaching rotation for medical residents to learn HIV pharmacotherapy. This interprofessional education (IPE) was deemed extremely valuable by postgraduate-year-3 residents who intended to have a future practice in HIV care. The overarching concept of this rotation was for the medical trainee to “become-the-pharmacist”, learning to recognize, prevent, and manage drug-related issues in HIV patients. Pharmacist-led IPE should be considered to support medical training in other highly specialized pharmacotherapeutic areas.